Productive farms – polluted water? Party political conflict about the implementation of the nitrates directive in Germany - Beulting, Miriam (2020)
Abstract: Agriculture puts major strains on Germany’s aquatic ecosystems because intensive livestock farming and overfertilization contaminate surface and groundwater bodies with nitrates. In order to address this environmental problem, Germany is obliged to implement the Nitrates Directive, a central water protection directive of the European Union. But ever since the adoption of this directive at the Euro-pean level in 1991, German policy-makers have struggled to properly implement it, both time- and content-wise. In June 2018, the European Court of Justice convicted the German government for the second time due to its non-compliance with the Nitrates Directive. This empirical observation forms the starting point of my research. The following thesis investigates why the German political decision-makers have repeatedly failed to produce timely and sufficient pol-icy outputs to comply with the European Nitrates Directives. Existing scientific literature points to the importance of party politics for policy responses to aquatic nitrate contamination. On that account, my thesis traces the German transposition of the Nitrates Directive between 1991 and 2018 with a focus on the policy process within the formal decision-making bodies of the national state, and the political parties operating within these decision-making bodies. In terms of theoretical framework, this research combines insights from cleavage theory, the Punctu-ated Equilibrium Framework and the EU implementation literature. Methodologically, it consists of a case study and analyses a variety of official documents (inter alia accounts of legislative debates, mo-tions, interpellations, bills and court judgments) with the aid of both qualitative and quantitative tech-niques of data analysis. The empirical findings confirm that party politics is key to understanding the policy process underlying the German transposition of the Nitrates Directive. Coupled with European pressure for policy reform, party-political cleavages helped put the nitrate issue onto the political agenda. However, the distribu-tion of policy-making competencies across decision-making bodies and the prevalence of coalition gov-ernments provided both proponents and opponents of strict nitrate policies among the political parties with possibilities to further their preferences. Besides, dissent between different state governments of the German bundesländer, and between environmental and agricultural policy-makers materialized. The policy process was therefore characterized by lengthy and controversial negotiations and trans-lated into policy compromises which fell short of the provisions of the Nitrates Directive